Implementing Eco Print in Making Environmentally Friendly Batik by DWP Asahan Regency - Wan Mariatul Kifti; Elly Rahayu; Risnawati Risnawati (STMIK Royal, 2022)
Abstract: Community service-themed events Applying Eco Print is Making Eco-Friendly Batik in the midst of the Dharma Wanita Persada (DWP) monthly routine activity of the PUPR Office of Asahan Regency. The monthly routine meetings that have been held by DWP members so far have been limited to routine activities. There has never been the empowerment of members through skill improvement to producing products that have economic value. This prompted the head of the DWP of the PUPR Service to decide to make activities that have more economic value in order to improve the welfare of DWP members. This activity lasts for one day using the community education method through lectures, discussions questions, and answers as well as the practice of making eco prints. Attended by as many as 25 participants Dharma Wanita and the STMIK Royal Lecturer Team. The purpose of this activity is to provide new knowledge and insights to participants on how to use simple materials that are environmentally friendly around us which can be used as creative endeavors during the pandemic. The implementation of the activity is divided into two sessions; The first is an exposure session about the meaning and benefits of eco print, the materials and tools used, and the techniques/methods for making eco prints. The second session is practice. Of the two methods of making eco prints, the steam/steam method was chosen to be practiced directly by the women of the DWP of the PUPR Office of Asahan Regency. This activity went well and got a good response from the participants, this can be seen from the activeness of the participants during the activity. The result is an increase in participants' knowledge and skills. Keywords: eco print; pounding; steamingAbstrak: Ditengah kegiatan rutin bulanan Darmawanita Persada (DWP) Dinas PUPR kabupaten Asahan yang telah dilakukan anggota DWP selama ini hanya terbatas pada kegiatan yang bersifat rutinitas biasa dan pengajian. Belum pernah dilakukan pemberdayaan anggota melalui peningkatan ketrampilan untuk menghasilkan produk yang bernilai ekonomis. Hal ini yang mendorong ketua DWP Dinas PUPR memutuskan untuk membuat kegiatan yang lebih bernilai ekonomis guna meningkatkan kesejahteraan anggota DWP. Metode dalam kegiatan ini yaitu pendidikan masyarakat melalui kegiatan ceramah, diskusi dan tanya jawab serta praktek pembuatan eco print. peserta dalam kegiatan ini adalahan ibu-ibu darmawanita yang dihadiri sebanyak 25 orang dan Tim dosen STMIK Royal. Tujuan dari kegiatan ini memberikan pengetahuan dan wawasan baru kepada peserta bagaimana memanfaatkan bahan-bahan yang sederhana ramah lingkungan disekitar kita yang bisa dijadikan sebagai usaha kreatif dimasa pandemi. Pelaksanaan kegaiatan terbagi dalam dua sesi; pertama sesi paparan tentang pengertian, dan manfaat dari eco print, bahan dan alat yang digunakan serta tehnik/metode pembuatan eco print. Sesi kedua adalah praktek pembuatan eco print. Kegiatan ini berjalan baik dan mendapatkan respon yang baik dari peserta, hal ini dilihat dari keaktifan peserta selama berlangsungnya kegiatan. Hasilnya adalah peningkatan pengetahuan dan keahlian peserta.Kata kunci: eco print; pounding; steaming